The Evolutionary Chromosome Translocation 4;19 in Gorilla gorilla is Associated with Microduplication of the Chromosome Fragment Syntenic to Sequences Surrounding the Human Proximal CMT1A-REP - Stankiewicz, Pawel; Park, Sung-Sup; Inoue, Ken; Lupski, James R. (Genome Research, 2001)
Many genomic disorders occur as a result of chromosome rearrangements involving low-copy repeats (LCRs). To better understand the molecular basis of chromosome rearrangements, including translocations, we have investigated the mechanism of evolutionary rearrangements. In contrast to several intrachromosomal rearrangements, only two evolutionary translocations have been identified by cytogenetic analyses of humans and greater apes. Human chromosome 2 arose as a result of a telomeric fusion between acrocentric chromosomes, whereas chromosomes 4 and 19 in Gorilla gorillaare the products of a reciprocal translocation between ancestral chromosomes, syntenic to human chromosomes 5 and 17, respectively. Fluorescence in situ hybridization (FISH) was used to characterize the breakpoints of the latter translocation at the molecular level. We identified three BAC clones that span translocation breakpoints. One breakpoint occurred in the region syntenic to human chromosome 5q13.3, between the HMG-CoA reductase gene (HMGCR) and RAS p21 protein activator 1 gene (RASA1). The second breakpoint was in a region syntenic to human chromosome 17p12 containing the 24 kb region-specific low-copy repeat-proximal CMT1A-REP. Moreover, we found that the t(4;19) is associated with a submicroscopic chromosome duplication involving a 19p chromosome fragment homologous to the human chromosome region surrounding the proximal CMT1A-REP. These observations further indicate that higher order genomic architecture involving low-copy repeats resulting from genomic duplication plays a significant role in karyotypic evolution.